Analysis of the Impact of Soybean Price Increases on the Availability of Soybean Stocks in the Somber Small Industrial Center Area of Balikpapan City - Wagimin; Kurnia, Wahyu Ismail; Fattah, Anwar (Journal La Lifesci, 2024)
Soybeans have a major role in the Indonesian economy, as they are the main source of raw materials in various industries. The objectives of this study are to identify factors affecting the increase in soybean prices, develop a dynamic system modelling related to the increase in soybean prices, calculate the availability of soybeans against the effect of soybean prices, and develop alternative policy recommendations to meet the needs of soybeans in the productivity of tempeh and tofu in Balikpapan, East Kalimantan. Applying system dynamics with Powersim uses a causal loop diagram to translate the variables that affect the availability of soybeans to meet the demand for soybeans. The results of this study show that the value of E1 for the sub-model of the rate of import activities is 1.0%, the availability of soybeans is 1.0%, and the need for soybeans is 0.99%, so E1 is declared Valid The value of E2 for the sub-model of the rate of import activities is 0%, the availability of soybeans is 0.622%, the need for soybeans is 0.325% so the value of E2 is declared valid. The forecasting variable of the rate of import activities in this study affects the availability and demand for soybeans. The availability variable influences the fulfilment of soybean demand. Balikpapan City can achieve soybean self-sufficiency for the following years if the needs have been met.